In vitro acaricidal activity of honey bee propolis against Haemaphysalis spp - Roghayeh Norouzi; Arman Shafaghat; Mohammad Saleh Mansoori Nour; Niloufar Dokht Jabbari; Abolghasem Siyadatpanah (Journal of zoonotic diseases (Online), 2025)
Ticks are responsible for transmitting of pathogenic microorganisms during their feeding process on the hosts. They also cause significant losses in livestock production and, in many cases, the death of infected animals. In recent decades, many efforts have been carried out to combat ticks by using natural compounds. The present study aimed to evaluate the acaricidal effect of the hydroalcoholic extract of honey bee propolis against Haemaphysalis spp. in vitro. The acaricidal activities of the propolis were considered at concentrations of 25, 50, and 100 mg/ml and negative and positive controls (distilled water and Cypermethrin) following 10, 30, and 60 minutes of exposure. In this experiment the spraying and contact methods were used, and all tests were repeated twice. The chemical composition of propolis was identification by Gas ChromatographyMass Spectrometry (GC–MS). Data were analyzed using GraphPad Prism software version 5.0. According to the results, propolis had an acaricidal effect; however, this effect was more potent in the spraying. The propolis showed a 100% mortality rate at 100 mg/ml concentrations after 60 min exposure. GC-MS investigation showed that Heptanone (48.65%) was the main ingredient of propolis. The results indicated that the hydroalcoholic propolis extract carry potent acaricidal ingredients and might afford new natural acaricidal compounds for the control of Haemaphysalis spp.